Fluxos de gases de efeito estufa [GEE] em florestas urbanas de São Paulo, SP: uma análise da contribuição das áreas verdes na resiliência da cidade - Souza, Raquel Cristina de (2019)
Since the Industrial Revolution, GHG emissions have grown every decade. Thus, the planet gets warmer every day, with extreme droughts and intense rains. The greenhouse gases are fundamental to keep the planet warm, but what worries is the expressive increase of their concentrations in the atmosphere. Human activities contribute to the emissions of these gases mainly through the deforestation and burning of fossil fuels. In cities, the forests lose space for the constructions that accompany the demography. In addition to the aesthetic value, urban forests play a fundamental and necessary role in the provision of ecosystem services, as well as representing urban reference. Because of their high potential for carbon sequestration, urban green soils can be considered good compartments in increasing city resilience to future climatic extremes. Thus, the objective of this work was to estimate the emissions of greenhouse gases - carbon dioxide - CO2, methane - CH4 and nitrous oxide - N2O - from the soil of four urban forests distributed in a center-periphery direction. The selected areas were Trianon Park [PT], Parque Alfredo Volpi [PAV], the State Park of Fontes do Ipiranga [PEFI] and Parque do Carmo [PC]. The effects of the size and / or geographic location of the urban forest on the GHG emission were evaluated, as well as the possible correlations between meteorological and edaphic factors (temperature and humidity). Regarding methane emissions, it was observed that the highest values were recorded in the PEFI and the lowest in the PT. In relation to CO2 and N2O, the highest medians recorded occurred in the PT, probably associated to the higher content of organic matter present in the soil. It was observed that some meteorological variables were related to GHG emissions, with emphasis on the average air temperature vs. emission of carbon dioxide and nitrous oxide, in addition to precipitation and water excess with these same gases, respectively. Rainfall showed an inverse relationship with CH4 emission. There was also a low association between the carbon [C] and nitrogen [N] stocks of the soil with CO2, and N2O emissions. Multidimensional non-metric multivariate analysis [NMDS] showed homogeneous groups, especially the PT that stood out from the other three study areas. The results show that urban forests function as good reservoirs of C and N and that public policies such as the Atlantic Forest Municipal Plan could be based on the results of this work to propose the increase of protected areas that contribute to the maintenance of important key processes to the resilience of cities to climate change. In summary, the soils showed low emitted GHG flows and high C and N stock potential. The PT was the park that stood out from the others, either for the emission of CH4 or the other compounds [CO2 and N2O], fact that reinforces that both the size of the area, its location or edaphic structure are relevant attributes in the dynamics of C and N in urban areas.